Effects of brief dialectical behavior therapy skills training on Malay-speaking school teachers: a controlled study - Keng, Shian-Ling; Pang, Nicholas Tze Ping; Tanin, Clarissa; Cheng, Yee Hsuen; Wong, Andrea; Nor Hadi, Noor Melissa (John Wiley and Sons, 2024)
School teachers are susceptible to mental health issues due to the challenging responsibilities the teaching profession entails. While several interventions have demonstrated effectiveness in improving teachers' social emotional competencies and mental health outcomes, little work has examined the potential of dialectical behavior therapy–skills training (DBT-ST) in improving teacher outcomes. This study aimed to assess the effects of a five-session, Malay-translated DBT-ST on psychological symptoms (anxiety, depression, stress, burnout), social-emotional competencies, DBT skills use, and dysfunctional coping in a sample of school teachers in East Malaysia. Fifty-three participants were recruited and assigned into DBT-ST or a control group, consisting of attending a mental health talk. Analyses showed that DBT-ST participants reported greater decreases in student-related burnout and dysfunctional coping, and greater increases in DBT skills use compared to the control group from pre- to post-intervention. There were no between-condition differences on changes in other mental health outcomes, though session attendance was linked positively to improvements in several outcomes in the DBT-ST condition. Analyses of post-intervention feedback indicated that brief DBT-ST was deemed acceptable and feasible among the research participants. In conclusion, DBT-ST holds promise as an intervention to lower student-related burnout and facilitate adaptive coping among school teachers.